2019
DOI: 10.1016/j.cgh.2018.11.028
|View full text |Cite
|
Sign up to set email alerts
|

Association Between Black Race and Presentation and Liver-Related Outcomes of Patients With Autoimmune Hepatitis

Abstract: Introduction & Aims Small studies have found that black patient with autoimmune hepatitis (AIH) patients present with more aggressive disease. We aimed to characterize the presentation and outcome in black and white patients with AIH. Methods We performed a retrospective study, collecting information from databases of patients with

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
30
1

Year Published

2019
2019
2022
2022

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 31 publications
(33 citation statements)
references
References 32 publications
(38 reference statements)
2
30
1
Order By: Relevance
“…Type 1 AIH is defined by the presence of antinuclear antibodies (ANAs) and/or anti-smooth muscle antibodies (SMAs), while type 2 AIH is defined by the presence of anti-liver-kidney microsomal 1 (LKM-1) antibody and/or antiliver cytosol type 1 (LC1) antibody (23,24). The pathogenesis of AIH is complicated and unclear, but it likely involves environmental factors (25), genetic factors, epigenetic factors (26,27), and a dynamic immunological microenvironment (28). It is widely accepted that both the initiation of the selfattack and the subsequent dysregulation of the immune system in the liver microenvironment contribute to the progressive process of liver damage.…”
Section: Aih: Current Research Statusmentioning
confidence: 99%
“…Type 1 AIH is defined by the presence of antinuclear antibodies (ANAs) and/or anti-smooth muscle antibodies (SMAs), while type 2 AIH is defined by the presence of anti-liver-kidney microsomal 1 (LKM-1) antibody and/or antiliver cytosol type 1 (LC1) antibody (23,24). The pathogenesis of AIH is complicated and unclear, but it likely involves environmental factors (25), genetic factors, epigenetic factors (26,27), and a dynamic immunological microenvironment (28). It is widely accepted that both the initiation of the selfattack and the subsequent dysregulation of the immune system in the liver microenvironment contribute to the progressive process of liver damage.…”
Section: Aih: Current Research Statusmentioning
confidence: 99%
“…In a single‐center study from the United States, black patients were more likely to present with liver failure compared with nonblack patients . Furthermore, a recent multicenter study showed that black patients with AIH presented at a younger age and had a greater risk of requiring LT when compared with white patients with AIH …”
Section: Epidemiologymentioning
confidence: 99%
“…(46) Furthermore, a recent multicenter study showed that black patients with AIH presented at a younger age and had a greater risk of requiring LT when compared with white patients with AIH. (47) Human leukocyte antigen (HLA) typing has been investigated in different populations with AIH. The…”
Section: Epidemiologymentioning
confidence: 99%
“…The ALFSG showed that blacks were significantly more likely to present with idiosyncratic DILI compared with whites (24.4% versus 14.9%, P = 0.009) . Recent European studies have also demonstrated that black patients with AIH present with more severe liver injury and are more likely to require transplant or die during follow‐up . Prospective studies of idiosyncratic DILI have also suggested that black patients are more likely to have poorer clinical outcomes including higher short‐term mortality compared with whites .…”
Section: Wait‐list Outcomes Among Status 1 Patientsmentioning
confidence: 99%
“…(5) Recent European studies have also demonstrated that black patients with AIH present with more severe liver injury and are more likely to require transplant or die during follow-up. (6) Prospective studies of idiosyncratic DILI have also suggested that black patients are more likely to have poorer clinical outcomes including higher short-term mortality compared with whites. (7,8) The reasons for the poorer outcomes when controlling for disease etiology are unknown but could be mediated by genetic or immunological factors.…”
Section: Wait-list Outcomes Among Status 1 Patientsmentioning
confidence: 99%